Formulation and evaluation of in situ ophthalmic gel of loteprednol etabonate - Shoaeba, Shaikh; Sharav, Desai; Jain, Hitesh; Sahu, Asit; Meshram, D. B. (Journal of Applied Pharmaceutical Research, 2021)
The aim of present study was to prepared ocular in-situ gel to increase the residence time of drug in cornea for improvement of ocular bioavailability of drug. In situ gel of Loteprednol etabonate was prepared by using carobopol 940 and different grades of HPMC in different ratios by pH triggered method. The prepared in situ gels were evaluated for pH, drug content, viscosity, gelling time, gelling strength spreadability and sterility testing. In vitro drug release study was carried by using diffusion cell with dialysis membrane. The drug content and pH of the formulation were found to be satisfactory. The gelling strength was found to be in the range of 34 seconds to 91 seconds. The viscosity and spredability of the formulations were found to be satisfactory. Formulation F5 containing 0.3 % carobopol 940 and 0.6 % HPMC K4M showed highest drug release of 80.30 %. The developed formulations showed sustained release of drug up to 8 hrs. From in-vitro drug release studies, it could be concluded that the developed in-situ gelling systems were thus a better alternative to conventional eye drops.